Factors contributing to residential overhang in Johor Bahru / Nurul Aqilah Kamal - Kamal, Nurul Aqilah (2023)
Property overhang is one of the well-known property issues in Malaysia. Johar Bahru is one of the states that contribute the highest property overhang in Malaysia and it follow by Penang and Selangor. Thus, this study being carried out at Johar Bahru, Johar. Based on the literature review that has been made from previous studies, there are few factors that contribute to residential overhang such as price, location, housing loan, building, feasibility study, public facilities and amenities and income level. The objective of this research is to determine the factors contributing to residential overhang and to examine the most important factors contributing to residential overhang in Johar Bahru. Then, the research technique that has been used is quantitative method and the data was collected using judgmental sampling. In this study, the online questionnaire has been distributed to those who work in real estate industry in Johar Bahru such as in valuation, estate agency and housing development which the respondent familiar with residential overhang issue.